Istota i przyszłość totalizmu w spojrzeniu polskich przedstawicieli nauk społecznych 1918–1939 - Kornat, Marek (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The study is devoted to the problem of the totalitarian regimes in the perception of Polish lawyers, sociologists, economists and historians in the interwar era 1918–1939. Poland in those times was one of the most vital centers in the Sovietology. Polish debates on the essential dimensions of the totalitarian systems belong to the most interesting from the perspective of seventy five years which divide us from the interwar era. The future of the phenomenon of the totalitarian or “totalist” regimes was discussed. Their durability was estimated as problematic. Polish lawyers viewed “total states” as extremely dynamic and based on the maximal mass mobilization, “ideocratic” legitimization of the authority and last but not last maximal concentration of power in the hands of the dictator or ruling elite.
Keywords: polska myśl polityczna; sowietologia; totalitaryzm; sowiecka Rosja